The Stock Market’s Reaction to Unanticipated Catastrophic Event - Karki, Dipendra (Journal of Business and Social Sciences Research, 2020)
Several factors influence the stock market; they trigger market over-or under-reactions. The paper aims to identify the effect of a major catastrophic event on stock returns. For this, daily data of stock market indices was used with a total of 210 observations and the effect of catastrophic event, Nepal Earthquake 2015, was tested using the method of event analysis for different event windows. The catastrophic event did not affect stock returns significantly and was resilient to earthquake-induced shocks. The event window (+2, +10) shows the higher and positive abnormal returns which depicts that the market has recovered from the shock in as many as three days. The study shows that stock market in Nepal is semi-strongly inefficient.